Carbon nanospheres as solid‐phase microextraction coating for the extraction of polycyclic aromatic hydrocarbons from water and soil samples. Issue 13 (18th May 2020) - Chang, Qingyun; Wang, Mengting; Zhang, Guijiang; Zang, Xiaohuan; Li, Hongda; Zhang, Shuaihua; Wang, Chun; Wang, Zhi
Abstract: A solid‐phase microextraction with carbon nanospheres coated fiber coupled with gas chromatographic detection was established for the determination of eight polycyclic aromatic hydrocarbons (naphthalene, biphenyl, acenaphthene, fluorine, phenanthrene, anthracene, fluoranthene, and pyrene) in water and soil samples. The experimental parameters (extraction temperature, extraction time, stirring rate, headspace volume, salt content, and desorption temperature) which affect the extraction efficiency were studied. Under the optimized conditions, good linearity between the peak areas and the concentrations of the analytes was achieved in the concentration range of 0.5‐300 ng/mL for water samples, and in the concentration range of 6.0‐2700 ng/g for soil samples. The detection limits for the analytes were in the range of 0.12‐0.45 ng/mL for water samples, and in the range of 1.53‐2.70 ng/g for soil samples. The method recoveries of the polycyclic aromatic hydrocarbons for spiked water samples were 80.10‐120.1% with relative standard deviations less than 13.9%. The method recoveries of the analytes for spiked soil samples were 80.40‐119.6% with relative standard deviations less than 14.4%. The fiber was reused over 100 times without a significant loss of extraction efficiency.